2013
DOI: 10.1080/17550874.2013.788567
|View full text |Cite
|
Sign up to set email alerts
|

Which processes drive fine root elongation in a natural mountain forest ecosystem?

Abstract: Background: Quantifying the dynamics of root growth is vital when characterising the role of vegetation in carbon cycling. Aims: We examined the temporal dynamics of root growth and responses to spatial (altitude, forest patchiness and soil depth) and biological factors (root diameter and root topology) in mid-montane and upper montane coniferous forest ecosystems. Methods: Using rhizotrons, two indicators were investigated: occurrence, i.e. the proportion of roots which had elongated since the previous measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…This assumption is supported by field measurements, showing low soil temperatures and more dry soil conditions during the dormant period 2010/2011 (Figure ). Comparable relations between root growth/development and (soil) climate were discussed in several studies [e.g., Pregitzer et al ., ; Alvarez‐Uria and Körner , ; Mao et al ., , ]. Both the coherent decrease of ASC and RLD (Figures a and b) and the significant relationship between ASC and RLD suggest (Figure a) that RLD is crucial for the formation of water‐stable aggregates in our experiment.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This assumption is supported by field measurements, showing low soil temperatures and more dry soil conditions during the dormant period 2010/2011 (Figure ). Comparable relations between root growth/development and (soil) climate were discussed in several studies [e.g., Pregitzer et al ., ; Alvarez‐Uria and Körner , ; Mao et al ., , ]. Both the coherent decrease of ASC and RLD (Figures a and b) and the significant relationship between ASC and RLD suggest (Figure a) that RLD is crucial for the formation of water‐stable aggregates in our experiment.…”
Section: Discussionsupporting
confidence: 54%
“…Even fine roots can store starch as well as nutrients, and the bigger the diameter, the more important this function is [ Danjon et al ., ]. When the photosynthesis rate is not sufficient, the stored starch can be used for root growth in times of low supplies, like early spring or winter season [ Danjon et al ., ; Mao et al ., , ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several authors detected no root productivity differences, or even higher fine root growth rates, at the treeline compared to stands at lower elevation (Graefe et al, 2008; Hertel and Schöling, 2011b; Mao et al, 2013). This apparent contradiction calls for a detailed study of root zone temperatures and tree root growth at the alpine treeline.…”
Section: Introductionmentioning
confidence: 98%
“…Responses of root elongation and longevity to climatic variations have usually been studied at the species level (Barlow and Rathfelder, 1985), or artificially in growth chambers (Lahti et al, 2005;Alvarez-Uria and Körner, 2007), which do not reflect the true conditions found in natural or mixed forests (Kubisch et al, 2017). Tree roots in heterogeneous temperate forest ecosystems can initiate and elongate during the winter, even when mean daily air temperatures are below freezing, as long as the soil temperature does not drop below 0 °C (Mao et al, 2013a;Radville et al, 2016). Optimal soil temperatures for conifer root growth vary from 6 to 15 °C [Picea abies (L.) Karst] and from 10 to 20 °C (Abies sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Optimal soil temperatures for conifer root growth vary from 6 to 15 °C [Picea abies (L.) Karst] and from 10 to 20 °C (Abies sp.) (Lopushinsky and Ma, 1990;Lyr, 1996;Alvarez-Uria and Körner, 2007;Nagelmüller et al, 2016), but periods of low or zero activity occur throughout the year (Mao et al, 2013a;Wang et al, 2018). However, few studies have characterized and quantified root active and dormant periods in the field, partially because of the relatively short duration of experimental studies on root growth and the assumption that root dormancy is synchronous with that of shoot dormancy (Eissenstat et al, 2005;Graefe et al, 2008;Abramoff and Finzi, 2015;Radville et al, 2016).…”
Section: Introductionmentioning
confidence: 99%